The 25th birthday and premature death of the open lung approach?—from science, through art, towards precision medicine - Bein, Thomas; Schultz, Marcus J. (Journal of Thoracic Disease, 2018)
Mechanical ventilation is a challenging intervention applied on a complex and very sensitive organ—the lung. The coexistence of open and collapse units in the lungs of patients with acute respiratory distress syndrome (ARDS) make this intervention even more challenging, as this dramatically increases the risk of harm caused by positive pressure ventilation. Indeed, this intervention, per se, has been identified as one of the most harmful intrusions in ARDS patients. From a physiologic standpoint it may seem attractive to open the collapsed lung units and to keep them open during the whole breath cycle. This ‘treats’ the at times life-threatening hypoxemia, consequently preventing a further deterioration of the other organs.